Magnetic Hybrid-Materials Multi-scale Modelling, Synthesis, and Applications - Odenbach, Stefan (De Gruyter, 2021)
Externally tunable properties allow for new applications of suspensions of micro- and nanoparticles in sensors and actuators in technical and medical applications. By means of easy to generate and control magnetic fields, fluids inside of matrices are studied. This monnograph delivers the latest insigths into multi-scale modelling, manufacturing and application of those magnetic hybrid materials.